THE CHILD OF SIX YEARS IN BASIC EDUCATION: PRODUCTION OF KNOWLEDGE IN THESIS AND DISSERTATIONS - Orlandi, Leonardo Angelo; Lima, Jose Milton [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
This research deals with the child's entry six years in elementary school and presents as an object of academic study of thematic productions such as from 2006 and 2011. Establishes as central objective: identify in the productions of the graduate education programs as the nine-year basic education have been implemented in respect of school subjects. The interest in investigating this topic that drift resulting from the entry of children six years for the first year of elementary school, are generating several paradoxes conducive to reflection in the form of designing education for the children. The research of a qualitative nature adopted as the bibliographic search methodology analyzed 42 dissertations and theses 4 located in different databases. The results has problematized that, unlike that prescribes the official documents, the changes were tiny in relation to the curriculum and to practices aimed at children of six years.
Keywords: Elementary school; Childhood; Childhood education